Optical band gaps and spectroscopy properties of Bim+/Eun+/Yb3+ co-doped (m = 0, 2, 3; and n = 2, 3) zinc calcium silicate glasses. Issue 10 (1st March 2023) - Dan, Ho Kim; Trung, Nguyen Dinh; Tam, Nguyen Minh; Ha, L. T.; Ha, C. V.; Zhou, Dacheng; Qiu, Jianbei
Abstract : VIS emission spectra of SZC- x Bi0.6Eu2Yb ( x = 1.0, 1.2, 1.4, 1.6, and 1.8 mol%) zinc calcium silicate glass samples under 320 nm excitation. Abstract : In this study, the indirect/direct optical band gaps and spectroscopy properties of Bi m + /Eu n + /Yb 3+ co-doped ( m = 0, 2, 3; and n = 2, 3) zinc calcium silicate glasses under different excitation wavelengths were investigated. Zinc calcium silicate glasses with the main compositions of SiO2 –ZnO–CaF2 –LaF3 –TiO2 were prepared by the conventional melting method. EDS analysis was performed to determine the elemental composition existing in the zinc calcium silicate glasses. Visible (VIS)-, upconversion (UC)-, and near-infrared (NIR)-emission spectra of Bi m + /Eu n + /Yb 3+ co-doped glasses were also investigated. Indirect optical band gaps and direct optical band gaps of Bi m + -, Eu n + - single-doped, and Bi m + –Eu n + co-doped SiO2 –ZnO–CaF2 –LaF3 –TiO2 –Bi2 O3 –EuF3 –YbF3 zinc calcium silicate glasses were calculated and analyzed. CIE 1931( x, y ) color coordinates for VIS and UC emission spectra of Bi m + /Eu n + /Yb 3+ co-doped glasses were determined. Besides, the mechanism of VIS-, UC-, NIR-emissions, and energy transfer (ET) processes between Bi m + and Eu n + ions were also proposed and discussed.